RELEVANSI FILSAFAT KONSTRUKTIVISME DALAM MENINGKATKAN PENDIDIKAN SISWA DI ERA DIGITAL - Nofi Arum Aqilla; Naili Aulia Rahmani; Arba’iyah Yusuf; Nazala Wahda Izzati (LPPM Universitas Cipta Mandiri, 2024)
This research focuses on the significance of constructivist philosophy in enhancing education in the digital era. Constructivism is a learning theory that highlights the role of students in constructing their own knowledge through interaction with the environment and personally constructed understanding. The digital era provides broad access to information and educational resources. The aim of this study is to assess the extent of constructivist philosophy's contribution to improving education in the digital age. The research method employed is qualitative, involving a literature review from multiple sources discussing constructivist philosophy. The findings emphasize the importance of the relevance of constructivist philosophy in enhancing education in the digital era, particularly concerning experiential learning, academic aspects, and related cognitive elements. The implications of the relevance of constructivist philosophy in the development of education in the digital age have a lasting impact and can serve as a foundation for progress in the education sector. Constructivist principles, which encourage students to be active and explore new knowledge, are pertinent given the current technological advancements where learning activities such as note-taking, drawing, and task completion have shifted to digital platforms. Many of today's generations engage in these activities, and can saving time. The constructivist approach has proven to support students in becoming independent and active learners in education, in line with the demands of the digital era.